Successful Treatment of a Patient with COVID-19-Induced Severe ARDS, Pneumothorax, and Pneumomediastinum with Awake vv-ECMO Implantation. (10th August 2022) - Umlauf, Julian; Eilenberger, Stefanie; Spring, Oliver
Abstract : Management of acute respiratory distress syndrome (ARDS) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still a challenge for the staff on intensive-care units (ICU's) around the world. Many of these patients are treated with invasive ventilation. Sometimes, the occurrence of pneumothorax and/or pneumomediastinum can complicate the course of the disease because initiation of invasive ventilation might be fatal in those patients. Venovenous extracorporal membrane oxygenation (vv-ECMO) is increasingly used to prevent patients with severe ARDS from hypoxia. However, clear recommendations for or against the initiation of vv-ECMO in awake patients are currently lacking. We present the case of a 42-year-old patient with COVID-19-associated severe ARDS, pneumothorax, and pneumomediastinum. To preserve sufficient oxygenation and to avoid invasive ventilation, we implanted a vv-ECMO while the patient was awake. The patient recovered and was discharged home 41 days after transfer to our hospital. We therefore suggest that awake implantation of vv-ECMO might be useful in a subgroup of patients with severe ARDS caused by SARS-CoV-2. However, further evidence is needed to verify our hypothesis.